2014
DOI: 10.1039/c4cc04338c
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals interactions in the self-assembly of 5-amino[6]helicene on Cu(100) and Au(111)

Abstract: A combination of Scanning Tunnelling Microscopy and Density Functional Theory simulations highlights the role of van der Waals interactions in the self-assembly of an aminohelicene on Cu(100) and Au(111).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…On Cu(100), however, [7]H crystallized into a twodimensional (2D) conglomerate phase consisting of homochiral domains built up from homochiral quadruplets. 19 Homochiral quadruplets were also observed for 5-amino [6]helicene on the same surface, 20 and alloying the Cu(100) surface with Sn caused racemate formation. 21 At small coverages homochiral quadruplets of [7]H were also observed on Ag(100), but with increasing coverage the racemic zigzag row motif dominated again the self-assembly.…”
mentioning
confidence: 85%
“…On Cu(100), however, [7]H crystallized into a twodimensional (2D) conglomerate phase consisting of homochiral domains built up from homochiral quadruplets. 19 Homochiral quadruplets were also observed for 5-amino [6]helicene on the same surface, 20 and alloying the Cu(100) surface with Sn caused racemate formation. 21 At small coverages homochiral quadruplets of [7]H were also observed on Ag(100), but with increasing coverage the racemic zigzag row motif dominated again the self-assembly.…”
mentioning
confidence: 85%
“…In both cases, the amino group does not induce polar interactions via hydrogen bonding but rather maximizes van der Waals interactions and drive the self-assembly. 301 The self-assembly of enantiopure (M) and (rac)-297 on Au(111) under UHV conditions was further investigated in 2016 (Figure 40a2). 295 The authors observed two rotational domains formed by rows of dimers oriented along the <1-11> Au crystallographic directions for the enantiopure aminohelicene being formed, according to DFT calculations, by flat-lying molecules in which the NH 2 groups govern the interaction with the surface (i.e., "N down"), whereas the C6 rings pack closely to maximize van der Waals interactions between neighboring molecules.…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%
“…At coverages up to one monolayer, enantiopure quadruplets were observed 14 . Interestingly, the same motif was identified for 5‐amino[6]helicene on the same surface, 15 but by alloying with tin racemate formation was induced 16 . A conglomerate‐to‐racemate transition was also observed on Ag(100) for [7]H. Enantiopure quadruplets at small coverage turned into racemic zigzag rows with increasing coverage 17 .…”
Section: Introductionmentioning
confidence: 53%